Penerapan Metode Ooad Dalam Implementasi Sistem Informasi Perpustakaan Berbasis Website Pada SMK XYZ - Alinda Nur Ismayani; Wiyanto; Ida Abdul Gopar (Teknik Informatika, Universitas Pelita Bangsa, 2023)
The school library is one of the facilities provided by the school as a supporter and supporter of the process of teaching and learning activities for students. The existence of a library is very helpful to increase or increase knowledge and insight for students at school. By increasing the maximum function of the library, it is also hoped that it will provide maximum education for students. At the XYZ Vocational School library, the library system is still manual, that is, the way to borrow and return books at the library is to still use handwriting. There are often errors in the process of borrowing and returning books, so it is often difficult for librarian to prepare reports. The absence of a library information system that is able to process borrowing and returning books quickly and accurately, print reports quickly, and can store data safely. With the system that will be built, the authors hope that this will not happen again, because the computerized system will be more supportive.-based library information system is website built using PHP with framework codeigniter and MySQL. System testing is done using the Black Box Testing method. The results of the research conducted is an implementation of a website using the OOAD at Tridaya Vocational High School Bekasi. The conclusion from the implementation of this library system is that it can carry out the process of borrowing and returning books quickly and accurately, print reports quickly, and can store data safely because it is integrated with the MySQL database.. Keywords: Library Information System, Website, OOAD.